Immunosuppressive, antimicrobial and insecticidal activities of inhibitor cystine knot peptides produced by teratocytes of the endoparasitoid wasp Cotesia flavipes (Hymenoptera: Braconidae) - Pinto, Ciro P. G. [UNESP]; Walker, Andrew A.; King, Glenn F.; Rossi, Guilherme D. [UNESP] (Wiley, 2022)
Teratocytes are specialized cells released by parasitoid wasps into their hosts. They are known for producing regulatory molecules that aid the development of immature parasitoids. We have recently reported the primary structures of cystine-rich peptides, including some containing inhibitor cystine knot (ICK) motifs, produced by teratocytes of the parasitoid Cotesia flavipes (Hymenoptera: Braconidae). ICKs are known for their stability and diverse biological functions. In this study, we produced four putative ICK peptides from the teratocytes of C. flavipes using solid-phase peptide synthesis or recombinant expression in E. coli, and investigated their functions on host immune modulation as well their potential to impair the development of two lepidopterans after ingestion of the peptides. In addition, the peptides were assayed against pathogens and human cells. The peptides did not influence total hemocyte count but suppressed cellular immunity, detectable as a reduction of hemocyte encapsulation (CftICK-I, CftICK-II, CftICK-III) and spread indexes (CftICK-IV) in the host. None of the peptides influenced the activities of prophenoloxidase and phenoloxidase in the hemolymph of larval Diatraea saccharalis (Lepidoptera: Crambidae). CftICK-I and CftICK-II with previously unknown function showed antifungal activity against Candida albicans but were non-toxic to human cells. CftICK-I, CftICK-II, and CftICK-III increased larval mortality and reduced leaf consumption of D. saccharalis, a permissive host for C. flavipes. The CftICK-III also increased larval mortality and reduced leaf consumption of Spodoptera frugiperda (Lepidoptera: Noctuidae), a non-permissive host for C. flavipes. This study highlights biological functions and biotechnological potential of ICK peptides from the teratocytes of C. flavipes.
Keywords: biocontrol; encapsulation; host regulation; Hymenoptera; parasitoid; phenoloxidase